MWCNT-COOH/PDMS based dry ECG electrodes for ambulatory ECG recordings - Gandhi, Bani; Raghava, N.S. (Materials letters, 2022)
•ECG electrodes fabricated using MWCNT-COOH and PDMS using molds.•Fabrication using 2-step dispersion: magnetic-stirring followed by ultrasonication.•Electrode concentration: increased capacitance, decreased resistance and impedance.•ECG results of 4 wt% fabricated electrodes comparable to Ag/AgCl electrodes.•Electrodes cause no adverse effects to skin; suitable for continuous ECG monitor. Highly conductive electrodes were fabricated using carboxylic functionalized Multiwalled Carbon Nanotubes (MWCNT-COOH), and Polydimethylsiloxane (PDMS) for continuous and long-term ECG monitoring. A two-step dispersion method was followed: first using magnetic stirring, and the second using ultrasonication. Thirteen electrodes with different concentrations of CNTs were fabricated using molds. The percolation threshold was observed at 4.5 wt%. These electrodes were subject to real-time and remote monitoring achieved by an Internet-of-Things (IoT) system.